Survey of musculoskeletal pain among dental clinician in Kulliyyah of Dentistry IIUM - Sukmasari, Susi; Ismail, Ahmad Faisal; Hamshah, Arbaatul Arroshikin Nazirah (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
This study aimed to determine the prevalent site of musculoskeletal pain and its associated risk factors among dental clinicians at the Kulliyyah of Dentistry, IIUM. A validated, pilot-tested self-administered questionnaires were distributed to 160 dental clinicians between March and June 2014 using convenience sampling method. Inclusion criteria includes dentist, clinical supervisors or clinical dental students. Dental clinicians whom were diagnosed with musculoskeletal disorders were excluded. Data obtained were recorded and analyzed using statistical package for the social science (SPSS) software version 19. Pearson correlation test was used to determine the association between the risk factors and pain sites. A total of 146 participants completed the questionnaire (91.3% response rate). The sample consist of 40 dentists (27.4%), 36 Year 3 students (24.7%) and 35 participants (24%) respectively from Year 4 and Year 5. There was high prevalence of neck pain (79.5%), back shoulder pain (74.7%) and lower back pain (71.9%) among dental clinicians. Significant correlation was found between physical activities with upper body region pain sites (r = 0.170, p=0.042) and lower body region pain sites (r = 0.221, p=0.008). There was a significant association between repetitive movements and wrist bending with upper and lower body region pain sites (r = 0.320, p = <0.001) (r = 0.278, p =0.001). No correlation between awkward postures with upper and lower body pain sites. This paper will relate to the Islamic teaching on moderation in working and in maintaining healthy lifestyle. The most prevalent site of musculoskeletal pain experienced by dental clinicians was at the neck area and the least was on the left arm. Repetitive movements, wrist bending and physical activities were associated with upper and lower body region pain sites.